Representasi Oksidentalisme dalam Film Gintama (2017) - Bayu Hastinoto Prawirodigdo (TUTURAN: Jurnal Ilmu Komunikasi, Sosial dan Humaniora, 2025)
Movies can influence audiences' perceptions of foreigners who are a minority group in society. There are positive and negative views of Westerners formed in Japanese films. The live-action movie “Gintama” uses the historical setting of Japan in the Bakumatsu period where Western countries succeeded in forcing Japan to open relations with foreign countries. This study attempted to determine the representation of occidentalism in Gintama movie. Using a qualitative descriptive research method that relies on Roland Barthes' semiotic analysis, this study analyzed the representation of occidentalism in this film through stages of analysis at the denotation level and connotation level. The analysis process involved documentation as a data collection technique. The results of the study showed the existence of denotative and connotative meanings that represent occidentalism in the historical story of Japan during the Bakumatsu period that is presented in this film. The results of the study indicated that occidentalism in the film Gintama is in accordance with the concept of occidentalism explained by Ian and Buruma where the West tends to be viewed negatively while Japan tends to be depicted positively.